Smart Travel Alarm – Hybrid app on Sencha 2.2 - Ankit Jain* , Neha Pamecha, Dr. Abbhilasha Mishra, (International Journal of Scientific Research and Management (IJSRM), 2017)
The proliferation of mobile platforms and technologies, along with the evolution of smart devices, provide plenty of opportunities for compelling applications. The key expectations are multifold, and include cost effectiveness, a single code base to work across multi platforms, an outstanding UI and faster delivery cycles. The modern applications are taking full advantages of the device features (GPS, camera...), form factors (tablets) and appealing user interaction. The best fit to accommodate most of the key mobile capabilities (single code base form factors, great UI) is to adopt mobile web technologies. This can be augmented by using the Hybrid approach to take full advantage of the device features in addition to the benefits listed above. SMART Travel Alarm is such a hybrid application which is developed on Sencha 2.2 framework. Sencha Touch enables us to quickly and easily create HTML5-based apps that work on mobile devices, and produce a native-app-like experience inside a browser or in a hybrid shell. Sencha Touch supports Android, iOS, Windows Phone, Microsoft Surface Pro and RT, and Blackberry devices.